Pengembangan multimedia pembelajaran berbasis aplikasi construct 2 untuk meningkatkan kemampuan pemahaman matematis dan self regulated learning siswa - Andriyana; Kariadinata, Rahayu; Nuraida, Ida (Papanda Publisher, 2025)
This study aims to develop instructional multimedia using the Construct 2 application to improve students’ mathematical understanding and self-regulated learning. The development follows the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation phases. The research focuses on four aspects: the development process, product validity, practicality, and effectiveness. Validation results from material and media experts indicate that the product is valid. Practicality is shown through positive feedback from teachers and students during implementation. Effectiveness is measured through improved student performance in mathematical understanding and self-regulated learning, as seen in pretest and posttest results. The findings suggest that the developed multimedia is valid, practical, and effective for use in mathematics learning. Thus, it can serve as an innovative and interactive learning tool to support student engagement and comprehension.